Effectiveness of intensive perioperative nutrition therapy among adults undergoing gastrointestinal and oncological surgery in a public hospital: study protocol for a pragmatic randomized control trial - Abdul A’zim, A’ishah Zafrah; Abu Zaid, Zalina; Mohd Yusof, Barakatun Nisak; Jabar, Mohd Faisal; Mohd Shahar, Aainaa Syarfa (BioMed Central, 2022)
Background: Perioperative malnutrition is common in patients undergoing gastrointestinal-oncology surgery and is associated with longer hospital stays, increased postoperative complications, poorer quality of life, and lower survival rates. Current practice emphasizes the role of early perioperative nutrition therapy as an early intervention to combat the postoperative complications of patients and the implementation is now widely adopted. However, there is still a lack of research on determining the effectiveness of intensive nutrition therapy and providing ONS perioperative locally. This becomes the significance of this study and serves as a basis for management and guideline in the local hospital settings. Methods: This is a pragmatic randomized control trial study where elective admitted patients will be randomly divided into the intervention (SS) or control (NN) group. All data will be collected during a face-to-face interview, anthropometric measurement, blood sampling (albumin, white blood count, hemoglobin, and c-reactive protein), handgrip strength, and postoperative complications. Group SS will be receiving a tailored lifestyle and intensively supplemented with oral nutrition support as compared to Group NN that will receive standard medical care. The primary outcome for this study is the length of stay in the hospital. Additional outcome measures are changes in biochemical profile and nutritional and functional status. The effects of intervention between groups on the outcome parameters will be analyzed by using the SPSS General Linear Model (GLM) for the repeated measure procedure. Discussion: The intervention implemented in this study will serve as baseline data in providing appropriate nutritional management in patients undergoing gastrointestinal and oncological surgery.